A unified framework for video summarization, browsing, and retrieval with applications to consumer and surveillance video - Xiong, Ziyou (Elsevier/Academic Press, 2006)
Large volumes of video content can only be easily accessed by the use of rapid browsing and retrieval techniques. Constructing a video table of contents (ToC) and video highlights to enable end users to sift through all this data and find what they want, when they want are essential. This reference puts forth a unified framework to integrate these functions supporting efficient browsing and retrieval of video content. The authors have developed a cohesive way to create a video table of contents, video highlights, and video indices that serve to streamline the use of applications in consumer and surveillance video applications. The authors discuss the generation of table of contents, extraction of highlights, different techniques for audio and video marker recognition, and indexing with low-level features such as color, texture, and shape. Current applications including this summarization and browsing technology are also reviewed. Applications such as event detection in elevator surveillance, highlight extraction from sports video, and image and video database management are considered within the proposed framework. This book presents the latest in research and readers will find their search for knowledge completely satisfied by the breadth of the information covered in this volume. * Offers the latest in cutting edge research and applications in surveillance and consumer video * Presentation of a novel unified framework aimed at successfully sifting through the abundance of footage gathered daily at shopping malls, airports, and other commercial facilities * Concisely written by leading contributors in the signal processing industry with step-by-step instruction in building video ToC and indices.